Red blood cell blood group A antigen level affects the ability of heparin and PfEMP1 antibodies to disrupt Plasmodium falciparum rosettes - Pontus Hedberg (BMC, 2021)
Abstract Background The histo-blood group ABO system has been associated with adverse outcomes in COVID-19, thromboembolic diseases and Plasmodium falciparum malaria. An integral part of the severe malaria pathogenesis is rosetting, the adherence of parasite infected red blood cells (RBCs) to uninfected RBCs. Rosetting is influenced by the host’s ABO blood group (Bg) and rosettes formed in BgA have previously been shown to be more resilient to disruption by heparin and shield the parasite derived surface antigens from antibodies. However, data on rosetting in weak BgA subgroups is scarce and based on investigations of relatively few donors. Methods An improved high-throughput flow cytometric assay was employed to investigate rosetting characteristics in an extensive panel of RBC donor samples of all four major ABO Bgs, as well as low BgA expressing samples. Results All non-O Bgs shield the parasite surface antigens from strain-specific antibodies towards P. falciparum erythrocyte membrane protein 1 (PfEMP1). A positive correlation between A-antigen levels on RBCs and rosette tightness was observed, protecting the rosettes from heparin- and antibody-mediated disruption. Conclusions These results provide new insights into how the ABO Bg system affects the disease outcome and cautions against interpreting the results from the heterogeneous BgA phenotype as a single group in epidemiological and experimental studies. Graphical Abstract